Family-centered services for children with complex communication needs: the practices and beliefs of school-based speech-language pathologists. (3rd April 2018) - Mandak, Kelsey; Light, Janice
Abstract: This study used an online focus group to examine the beliefs and practices of school-based speech-language pathologists (SLPs) who served children with complex communication needs regarding their provision of family-centered services. Participants revealed that despite their desire for family involvement and reported beliefs in the importance of family-centered services, there were barriers in place that often limited family-centered service provision. Across the SLPs, many were dissatisfied with their current provision of family-centered services. The SLPs varied in their reported practices, with some reporting family-centered services and others, professional-centered services. Future research is recommended in order to investigate which factors contribute to the variation among SLPs and how the variation impacts children who require augmentative and alternative communication (AAC) and their families. Potential clinical implications for in-service and pre-service SLPs are discussed to improve future family-centered AAC services.